Drug like HSP27 cross linkers with chromenone structure ameliorates pulmonary fibrosis - Yoo, Young Jo; Jeon, Seulgi; Jin, Hee; Won, Hee Yeon; Jeong, Mi Gyeong; Cho, Yeseul; Hwang, Eun Sook; Na, Younghwa; Cho, Jaeho; Lee, Yun-Sil (Frontiers in Pharmacology, 2023)
Background: Pulmonary fibrosis (PF) is a progressive lung disease characterized by fibroblast accumulation and collagen deposition, resulting in lung scarring and impaired gas exchange. Current treatments for idiopathic pulmonary fibrosis (IPF) have limited efficacy and significant side effects. Heat shock protein 27 (HSP27) has emerged as a potential therapeutic target for PF due to its involvement in fibrotic processes. However, effective HSP27 inhibitors for PF treatment are still lacking. Methods: To assess the anti-fibrotic effects of NA49, we utilized murine PF models induced by radiation (IR) or bleomycin (BLM). We administered NA49 to the PF mice and evaluated its impact on lung fibrosis progression. We also investigated the molecular mechanisms underlying NA49's effects, focusing on its inhibition of EMT-related signaling pathways. Results: In our study, we evaluated the potential of a novel HSP27 inhibitor, NA49, in preclinical models of PF. NA49 effectively suppressed PF development in radiation and bleomycin-induced PF models. It reduced fibrosis, inhibited NFkB signaling, and downregulated EMT-related molecules. Importantly, we evaluated the safety profile of NA49 by assessing its impact on DNA strand breakage. Compared to previous HSP27 inhibitors, NA49 showed lower levels of DNA damage in human lung epithelial cells, and suggests that NA49 may have reduced toxicity compared to other HSP27 inhibitors. Overall, our results demonstrate that NA49 effectively inhibits PF development in preclinical models. It reduces lung fibrosis, inhibits EMT-related signaling pathways, and exhibits improved safety profiles. These findings highlight the potential of NA49 as a promising candidate for the treatment of PF. Conclusion: NA49 exhibited significant anti-fibrotic effects, inhibiting fibrosis development and EMT-related signaling pathways. Moreover, NA49 showed improved safety profiles compared to previous HSP27 inhibitors.